The Influence of Organizational Communication in Improving Safety Culture in PT. XYZ - Marlinda Irwanti Poernomo; Bambang Sulistyo P; Siska Armawati Sufa (Ikatan Sarjana Komunikasi Indonesia, 2022)
It is expected that an organization will conduct a communication process in building a culture. The management of a company presents some policies and responsibilities through verbal and non-verbal messages continuously. It aims to shape a safety culture behaviour for the organization members of the company themselves. Research of the internal and external organizational communication influences the effort to improve Safety Culture through conceptual system or communication model. In addition, it also aims to improve the influence of risk and K3 communication including in the implementation of Safety Culture in PT. XYZ’s work environment. This study used quantitative method in order to easily understand communication process in internal and external organizational communication. There are 162 respondents used as sample in this research. The data sampling technique uses Probability Sampling method with Proportionate Stratified Random Sampling. The analysis method that was used first for linear regression analysis was normality test. Then, the researchers conducted a validity and reliability test. The hypothesis test used significance test simultaneously and partial significance test. The research data was analysed through the SPSS 24 software. This test was conducted by seeing the value of F that was present in ANOVA table, significance level that was used was 0,05. Climate and satisfactory in communication developed a measurement in safety culture comprehensively that included safety culture instruments that was categorized into independent variables (X). It included safety culture indicators, safety culture climate, safety management system or situational, safety behaviour, and organizational communication.